SEMINAR ON AUTO-PROFIT FROM SOCIAL MEDIA (NO NEED TO BE A CELEBRITY AS LONG AS YOU KNOW THE TRICKS) - Muhammad Fikry Januar Januar; Sekar Fauziah Larasati; Solihin; Imma Ismaniar; Dede Ibrahim Maulana; Mochamad Anjar Albagja; Endra Abdul Hadi; Nurdiansyah Permana (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
The development of social media offers new economic opportunities, but public understanding of strategies for utilizing it to generate income remains low. Lack of digital literacy, digital marketing skills, and content creation skills are major obstacles to optimizing social media as an economic tool. The seminar "Automatic Profit from Social Media: No Need to Be a Celebrity, Just Know the Tricks" was held to address these issues, aiming to improve participants' understanding of digital marketing strategies, personal branding, and social media monetization techniques. The implementation method used a participatory approach through interactive lectures, case studies, group discussions, and evaluation through pre- and post-tests. The results showed a significant increase in participants' understanding, with an average assessment score increasing by 25 points after the training. This seminar successfully improved participants' digital literacy and practical skills in optimizing social media as a source of income, thus potentially encouraging community economic independence.